2021
DOI: 10.1111/ped.14417
|View full text |Cite
|
Sign up to set email alerts
|

The effects of nutritional status and intervention on pulmonary functions in pediatric cystic fibrosis patients

Abstract: Background: Cystic fibrosis (CF) causes malabsorption of nutrients that exacerbate pulmonary problems. Nutritional interventions can improve pulmonary functions. We aimed to evaluate the effects of nutritional intervention in CF patients with malnutrition, and to determine if there is a correlation between nutritional status and pulmonary functions. Methods: The study included 143 CF patients (67 females) with a mean 2 year follow-up time. Patients' sociodemographic data, presenting symptoms and history were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 29 publications
1
5
1
Order By: Relevance
“…A parallel decrease in the nutritional status and respiratory function would negatively affect the prognosis and quality of life [103]. Kilinc et al reported that well-nourished patients had significantly higher lung function test scores than the other undernourished group [104]. Although in our study we did not have obese patients by BMI, there were two overweight patients (8 and 13 years) and obesity (2 and 25 years) by the waist-height index.…”
Section: Nutritional Statuscontrasting
confidence: 51%
“…A parallel decrease in the nutritional status and respiratory function would negatively affect the prognosis and quality of life [103]. Kilinc et al reported that well-nourished patients had significantly higher lung function test scores than the other undernourished group [104]. Although in our study we did not have obese patients by BMI, there were two overweight patients (8 and 13 years) and obesity (2 and 25 years) by the waist-height index.…”
Section: Nutritional Statuscontrasting
confidence: 51%
“…Most of the studies suggest that attaining a BMI below the 10th percentile (roughly corresponding to a z-score < −1.0) is indicative of malnutrition. With this in mind, published data suggest that malnutrition prevails in 12-74% of pediatric patients with CF [21][22][23][24][25][26]. Some earlier studies using the stricter cut-off of the 15th BMI percentile to identify malnutrition support similar findings, with malnutrition being diagnosed in 20-30% of pediatric patients [27][28][29][30].…”
Section: Discussionmentioning
confidence: 78%
“…Previous studies on patients with cystic fibrosis mostly focused on the effects of nutritional status on lung development and pulmonary function. Kilinc et al [ 18 ] studied 143 patients with cystic fibrosis who were followed up for 2 years. They found that appropriate nutritional support could maintain or improve the respiratory function of children with cystic fibrosis.…”
Section: Discussionmentioning
confidence: 99%